Male protagonists and Haitian (un)inhabitability in Kettly Mars’s L’Heure hybride and Aux frontières de la soif - Alessandra Benedicty (Francosphères)
Ultimately, the relationship between ‘staying’ and ‘leaving’ informs not only discussions among Haitian writers and the literary critics who study their works, but also undergirds tensions among Haitians within Haiti and throughout the diaspora, and implicates complex issues of social class, race, and language. These are themselves informed by a larger web of the varying relationships between Haiti and the international community, an international community that has more or less actively been present in the gestation of Haiti’s government and civil society. As such, this article uses as its point of departure what is a charged category of analysis: Martin Munro’s theorization of ‘uninhabitability’ and Nadève Ménard’s consideration of its counterpart ‘inhabitability’. In my article, to address what is the ‘incontournable’ issue of gender-based violence (GBV) depicted in several of Kettly Mars’s novels, and notably in L’Heure hybride (2005) and Aux frontières de la soif (2013), I work with Walter D. Mignolo’s notion of ‘border thinking’.